2015
DOI: 10.1128/iai.02559-14
|View full text |Cite
|
Sign up to set email alerts
|

Role of Anaerobiosis in Capsule Production and Biofilm Formation in Vibrio vulnificus

Abstract: Vibrio vulnificus, a pervasive human pathogen, can cause potentially fatal septicemia after consumption of undercooked seafood. Biotype 1 strains of V. vulnificus are most commonly associated with human infection and are separated into two genotypes, clinical (C) and environmental (E), based on the virulence-correlated gene. For ingestion-based vibriosis to occur, this bacterium must be able to withstand multiple conditions as it traverses the gastrointestinal tract and ultimately gains entry into the bloodstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 74 publications
1
25
0
Order By: Relevance
“…As production of these polysaccharides is metabolically expensive, there must be a key ecological role for their production in the estuarine environment, especially under hypoxic stress. Consistent with our previous in vitro results, the expression of wzb was decreased during conditions where oxygen was limited; however, the second CPS type and EPS production did not follow that trend [Phippen and Oliver, 2015b].…”
Section: In Situ Gene Expression Profilessupporting
confidence: 92%
See 2 more Smart Citations
“…As production of these polysaccharides is metabolically expensive, there must be a key ecological role for their production in the estuarine environment, especially under hypoxic stress. Consistent with our previous in vitro results, the expression of wzb was decreased during conditions where oxygen was limited; however, the second CPS type and EPS production did not follow that trend [Phippen and Oliver, 2015b].…”
Section: In Situ Gene Expression Profilessupporting
confidence: 92%
“…We investigated a variety of genes involved in multiple categories, including capsular polysaccharide (CPS)/exopolysaccharide (EPS) production, motility and attachment, global gene regulation, putative virulence factor production, stressosome formation, and general metabolism (Figure ). Many of these genes have been previously shown to be differentially regulated by V. vulnificus in response to environmental and host stressors and/or those that have been implicated in virulence [ Bisharat et al , ; Phippen and Oliver , , ; Williams et al , ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In regard to biofilm, temperature did not affect its formation, unless in the conditions assayed. In fact, some studies reported that this process is controlled by iron, among other external factors (Phippen and Oliver, 2015;Pajuelo et al, 2016;Chodur and Rowe-Magnus, 2018) (Figure 7).…”
Section: Attachment Multiplication and Biofilm Formationmentioning
confidence: 99%
“…Rutherford et al (2007) also found differences in the amount of Listeria on shrimp which were stored in air, vacuum, and map packaging (100% CO 2 ) at 3, 7, and 10 • C. Moreover, V. parahaemolyticus and L. monocytogenes could form bacterial biofilms to survive on food processing surfaces under anaerobiosis or aerobiosis (Voidarou et al, 2011;Valimaa et al, 2015;Perez-Ibarreche et al, 2016;Song et al, 2016). In an early study, the biofilm formation of Vibrio vulnificus was reduced due to the lack of oxygen (Phippen and Oliver, 2015). However, Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%